Silica Nanoparticles as Adhesives for Biological Tissues? Re‐Examining the Effect of Particles Size, Particle Shape, and the Unexpected Role of Base. (20th November 2017) - Liu, Hui; Peng, Yanfen; Yang, Cangjie; Wang, Mingfeng
Abstract: Development of new, effective, and patient‐friendly adhesives for biological tissues is important for medical and surgical practices such as bleeding control and organ repairing. While some commercially available silica nanoparticles such as LUDOX SM‐30 have shown adhesive properties for biological tissues, the role of inorganic base present in the adhesive properties of the silica nanoparticles has not been examined. Moreover, it remained unclear how the size and the shape of silica nanoparticles affect the adhesion properties. To address these questions, synthesis and characterization of a series of uniform silica nanostructures with different sizes and shapes is carried out. Unexpectedly, none of the synthesized silica nanostructures without additional inorganic base shows adhesion properties against liver tissues. Such surprising phenomena motivate to examine other factors in the commercial silica nanoparticles as tissue adhesives, and reach a conclusion that the inorganic base plays a key role in the adhesion properties. It is believed that this study answers the important question whether silica nanoparticles can act as biological adhesives or not. The conclusion also gives a lesson to other scientists and engineers in design and exploration of new biological adhesives. Abstract : The concept of using nanoparticles as biological adhesives is re‐examined using a series of silica particles with controlled sizes and shapes. Experimental results demonstrate that the inorganic base such as NaOH and KOH play a key role in the tissue adhesion of pig liver.